STUDENTS’ PERCEPTIONS ON SPOTIFY APPLICATION IN IMPROVING ENGLISH PRONUNCIATION - Risyal Arief Arsyawan; Jafar Shodiq; Sari Wulandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT Listening music through music streaming has become part of tertiary students’ activities. Music streaming is one of the media that can improve students' English pronunciation. The purpose of this research was to investigate three students’ perceptions from different Universities in Indonesia on the use Spotify application in improving English pronunciation. A qualitative research method with thematic analysis was applied in this research and the subjects of this research were four students from SMP 21 Semarang, Grade IX H, two of whom had good pronunciation and the other two were average, based on parameters related to Spotify features such as student interest and student motivation (Andriani et al., 2018; Rahmania & Mandasari, 2021). Three themes were identified from the interview results: Easy and flexible accessibility features, Engaging media for learning, and Practicing English pronunciation. The findings of this research revealed that the use of Spotify features for English pronunciation improved students' pronunciation, particularly in terms of words and meanings. The two students with good pronunciation paid attention to the elements of English pronunciation, such as vowels, stress, rhythm, pitch, and intonation. However, the students with average pronunciation only listened to the songs.